Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di Sekolah Wijaya Kusuma Kota Jakarta Utara - Nadya Stephanie Hardiyanti; Natal Indra (Jurnal Riset dan Inovasi Manajemen, 2026)
This study aims to examine the effect of work motivation and work environment on employee performance at Wijaya Kusuma School, North Jakarta, both partially and simultaneously. This research employed a quantitative approach using a survey method. The population consisted of all employees of Wijaya Kusuma School, North Jakarta, with a total sample of 87 respondents selected using a saturated sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. The data analysis techniques included instrument testing, classical assumption tests, and hypothesis testing using multiple linear regression analysis, F-test, t-test, and coefficient of determination. Data processing and analysis were conducted using SPSS version 25. The results indicate that work motivation has a positive and significant effect on employee performance. In addition, the work environment also has a positive and significant effect on employee performance. Simultaneously, work motivation and work environment significantly influence employee performance at Wijaya Kusuma School, North Jakarta. These findings suggest that improving employee motivation and creating a supportive and conducive work environment are essential strategies for enhancing employee performance in educational institutions.